Quality of refrigerated raw milk produced in the microregion of Pires do Rio, Goiás, Brazil (Research, Society and Development, 2020)
The aim of the present study was to analyze the somatic cell count (SCC), total bacterial count (TBC), fat, protein, lactose, total dry extract (TDE) and defatted dry extract (DDE) of milk produced in the Pires do Rio – Goiás, Brazil, taking into account the parameters described in Normative Instruction 76, of November 26, 2018. Milk samples were collected from 86 farms with different types of milking, which were analyzed by the Quality Laboratory. Milk from the Center for Food Research of the School of Veterinary and Animal Science of the Federal University of Goiás, in the city of Goiânia. Data were submitted to the nonparametric Kruskal-Wallis test for comparison of median values, adopting a significance level of 5%. Of the properties analyzed, 26 have manual milking and 60 mechanized milking, all parameters were observed in accordance with the minimum and maximum limits defined by IN 76/2018, with the average values of SCC and TBC, 356.441x 10³ cells per mL-1 and 60.047. x10³ colony forming units per mL-1, respectively. From the analyzed parameters it was possible to notice that the milk from the mechanical milking presented higher levels of SCC than the samples from the manual milking, besides the disagreement regarding the protein and lactose values between the different types of milking. Concluding that the milk produced in the Pires do Rio microregion – Goiás, extracted by mechanical and manual milking, is in accordance with the standards established by IN 76/2018.